2008
DOI: 10.1080/01639360802261920
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Genetic and Environmental Determinants of Taste with Food Preferences in Older Adults

Abstract: Individual differences in the ability to detect bitter tasting compounds, such as phenylthiocarbamide (PTC) or its derivative, 6-n-propylthiouracil (PROP) has long been recognized as a common genetic trait. This observation has been proposed to explain some of the variability in the dietary habits of a population. Several members of the TAS2R receptor gene family encode taste receptors on the tongue, and genetic polymorphisms of TAS2R38 have been associated with marked differences in the perception of PTC and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…And, at concentrations above the detection threshold, the perceived intensity of the stimulus may vary between individuals. This variation in taste sensitivity may affect food liking as well as food choice [1][6] and may ultimately impact health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…And, at concentrations above the detection threshold, the perceived intensity of the stimulus may vary between individuals. This variation in taste sensitivity may affect food liking as well as food choice [1][6] and may ultimately impact health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Age, culture, appetite, cost and availability are also important determinants [33] . The role that genetic variability in taste perception has in eating behavior or health outcomes may be more apparent among younger subjects since environmental and physiological factors may have had less of an impact on the eating behavior of these individuals [34] . In a recent review on the nutritional implications of genetic taste variation, it was noted that this wide variety of food selection determinants has been largely ignored in studies of this phenotype [35] .…”
Section: Discussionmentioning
confidence: 99%
“…Although the association between age and the expression of bitter taste receptors is controversial and the relationship may not be consistent [24], it was reported to be greatly influenced by various environmental factors [25]. For instance, we previously reported that bitter taste receptor expression was influenced by exposure to a wide variety of foods; in other words the more food types people experience, the greater their expression of bitter taste receptors (presented at 15 th International Symposium on Olfaction and Taste at San Francisco).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this is that the expression of bitter taste receptors is so sensitive to environmental factors that it is conceivable that the expression would decrease to zero very quickly [25]. …”
Section: Discussionmentioning
confidence: 99%